REPRESENTASI IDENTITAS SUNDA DALAM CERPEN ABAH JEUNG LAPTOP KARYA HIKMAT NUGRAHA - Nurullah, Maria Fiducia; Rahayu, Lina Meilinawati; Priyatna, Aquarini (JURNAL PESONA, 2017)
This research described Sundanese identity on âAbah jeung Laptopâ by Hikmat Nugraha. The research analised narrative struckture and setting on the short story. This study aimed to describe how the representasion of Sundanese identity on contemporary literature. This research used qualitative method and literature study for collecting the data. In analyzing the data, the researcher used narrative struckture method by Mieke Bal to describe how narrator and fokalisator on the short story affected how Sundanese identity be representasion on this story. The analysis showed the representasion of Sundanese identityon the actors on story changed because of modernize. The struggle which representing by the actors showed how shifting of identities was very difficult but identities always changed because of history and cultures change.